Membakeries: AI-Powered Custom Cake Ordering System - Sahanuan, Nurulaina Nisa; Hamzah, Mohd Hamdi Irwan (Applied Information Technology And Computer Science, 2025)
The rapid adoption of digital technology has transformed customer communication, prompting businesses to embrace online platforms for improved efficiency and accessibility. Membakeries, a neighbourhood bakery specializing in personalized cakes and desserts, faces challenges with its manual ordering process, leading to inefficiencies, limited customer reach, and potential errors. This project aims to develop a robust online ordering system comprising a web-based platform and a mobile application. Using the Scrum Agile methodology, iterative development and continuous feedback were implemented across initiation, planning, implementation, and refinement phases. The web platform was built with the Laravel Framework using the Model-View-Controller (MVC) pattern and PHP, while the mobile application employed Flutter in Android Studio. Modules include catalogue management, order processing, secure payments, and real-time order tracking. The resulting system enhances operational efficiency, ensures scalability, and elevates customer satisfaction, positioning Membakeries competitively in the online bakery market with sophisticated customization and seamless user experiences.